The Influence of Mental Health on Employee Performance with Physical Activity as a Moderating Variable - Erwanto, Erwanto; Elshifa, Aria; Wibowo, Teguh Setiawan; Yakin, Ikram; Salampessy, Maryam (LPPM Institut Nasional Laa Roiba Bogor, 2024)
ABSTRACT. Researchers believe that mental health can have a positive relationship and a significant influence on employee performance because mental health, which consists of psychological health and intellectual health, can make employees work stably, measurably, efficiently and effectively in taking every step and making every decision. facing difficulties. Apart from that, researchers also believe that the effect will be more significant if accompanied by good physical activity which leads to good physical health. This research is quantitative research with an explanatory approach. The data used in this research is primary data that researchers obtained from distributing a questionnaire containing 14 items consisting of 6 Mental Health variable question items, 4 Employee Performance variable question items, and 4 Physical Activity variable question items. This data can also be called primary data. This research was conducted on 300 Bank Permata employees spread throughout Indonesia. The resluth in this research show good Mental Health can have a positive relationship and a significant influence on Employee Performance because Mental Health which consists of Mental Health and Intellectual Health can make employees more focused at work, more efficient in completing targets, and more effective in solving existing problems. Therefore, the results of the first row of path coefficients in this study show that the mental health variable can have a positive relationship and a significant influence on employee performance due to the positive P-Values and being below the 0.05 significance level, namely 0.021. Apart from that, the results of the second row of the third table of path coefficients show that the beliefs and assumptions of the two researchers can be fulfilled because the P-Values are positive and are below the significance level of 0.05, namely 0.000, because good physical activity can make the body healthy so that employees can work with focus, fit, and be able to complete any target without hindrance. Moreover, this is accompanied by good mental health and intellectual health. In this way, employee performance can be easily achieved. Based on this, the first and second hypotheses in this research can be accepted.